2006
DOI: 10.1111/j.1741-4520.2006.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility in the neural tube defects induced by ochratoxin A in the genetic arhinencephaly mouse,Pdn/Pdn

Abstract: It is well known that ochratoxin A (OTA) induces neural tube defects (NTDs) in mice. In the present study, OTA was administered to the genetic polydactyly/arhinencephaly mouse (Pdn/Pdn) to investigate the synergistic effect between gene and environmental toxin. OTA treatment on day 7.5 of gestation increased NTDs in the Pdn/Pdn mouse. The responsible gene for Pdn/Pdn is Gli3. So, it was speculated that specific susceptibility for OTA in the Pdn/Pdn mouse embryo may be due to the severe depression of Gli3 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
10
0
3
Order By: Relevance
“…No ectopic and/or over-expression of Shh was detected in the Gli3 depressed Pdn/Pdn embryos (Figs 2; 3B; 4H). It was reported that Shh is upstream of Gli3 in the signaling pathway (Ming et al 1998), and that depression of Gli3 expression does not affect to Shh expression (Aoto et al 2002;Lamm et al 2002;te-Welscher et al 2002;Altaba et al 2003;Kuschel et al 2003;Ohta et al 2006), being consistent with the present data (Figs 2; 3B; 4H). Gli3 mutants exhibit an expansion of Fgf8 expression ( Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No ectopic and/or over-expression of Shh was detected in the Gli3 depressed Pdn/Pdn embryos (Figs 2; 3B; 4H). It was reported that Shh is upstream of Gli3 in the signaling pathway (Ming et al 1998), and that depression of Gli3 expression does not affect to Shh expression (Aoto et al 2002;Lamm et al 2002;te-Welscher et al 2002;Altaba et al 2003;Kuschel et al 2003;Ohta et al 2006), being consistent with the present data (Figs 2; 3B; 4H). Gli3 mutants exhibit an expansion of Fgf8 expression ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Real-time PCR method has been described previously (Ohta et al 2006;Katagiri et al 2007). After removing the yolk sac membrane for genotyping, the head region of six embryos in both +/+ and Pdn/Pdn on day 9 of gestation were collected and frozen in liquid nitrogen and total RNA was isolated using the RNeasy Mini Kit (QIAGEN, Tokyo, Japan).…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…A 180 bp band with etn11F and R6 was obtained in Pdn/Pdn embryos. This genotyping allowed us to analyze the alteration of gene expression in early Pdn/Pdn mouse embryos prior to morphological signs of genotype recognition (Ueta et al 2004;Maekawa et al 2005;Naruse et al 2005;Ohta et al 2006;Katagiri et al 2007;Ueta et al 2008). To determine the sex of the embryos, we used the Sry gene sequence on the Y chromosome to obtain 274 bp PCR products in the male embryos using the primers shown in Table 1.…”
Section: Genotyping Methodsmentioning
confidence: 99%
“…OTA (Sigma-Aldrich Chemie Gmbh, Steinheim, Germany) was dissolved with 0.1 M NaHCO3 in distilled water adjusted to pH 7.4 with HCl. After mating Pdn/+ females with Pdn/+ males, 2 mg/kg OTA was administered intraperitoneally to the Pdn/+ females on day 7.5 of gestation at 18.00 hours as described in a previous study (Ohta et al 2006). Fetuses on day 18 of gestation were recovered for external observations, and conceptuses on day 9 were recovered for gene expression analysis.…”
Section: Ota Treatmentmentioning
confidence: 99%